Multi-mode bonding ruthenium composite luminescent material based on COF carrier and preparation method thereof

By combining the covalent organic framework material PTCA-COF with the bipyridine ruthenium compound, the problem of easy detachment of ruthenium complexes on the surface of solid electrodes was solved, and a ruthenium composite luminescent material with high conductivity and high stability was achieved, which is suitable for fields such as electrochemiluminescence and biosensing.

CN120647868APending Publication Date: 2025-09-16BINZHOU WEIQIAO NATIONAL SCIENCE & TECHNOLOGY ADVANCED TECHNOLOGY RESEARCH INSTITUTE +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510931724.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-07
Publication Date
2025-09-16

AI Technical Summary

Technical Problem

Ruthenium complexes are easily detached from the surface of solid electrodes, resulting in unstable sensing signals and waste of resources. The luminescence effect and stability of existing carrier materials such as MOF-UiO-67(N) need to be improved.

Method used

The covalent organic framework material PTCA-COF is used as a carrier and combined with bipyridine ruthenium compounds through π-π bonding or covalent bonding to form Ru-Au@COF or Ru-PEI@COF composite materials, thereby improving the conductivity and stability of the material.

Benefits of technology

The high conductivity and high stability of ruthenium composite luminescent materials are achieved, and the electrochemiluminescence performance is improved, making it suitable for electrochemiluminescence, biosensors and flexible optoelectronic devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120647868A_ABST
    Figure CN120647868A_ABST
Patent Text Reader

Abstract

The invention discloses a COF carrier-based multi-mode bonded ruthenium composite luminescent material and a preparation method thereof, the ruthenium composite luminescent material comprises a covalent organic framework material (PTCA-COF) and a bipyridine ruthenium compound connected to the PTCA-COF through pi-pi bonding or covalent bonding, and the PTCA-COF is formed by connecting perylene-3, 4, 9, 10-perylene-3, 4, 9, 10-perylene-3, 10-perylene-3, 10-perylene-3, 10-perylene-3, 10-perylene-3, 10-perylene-3, 10-perylene-3, 10-perylene-3, 10- The preparation method comprises the following steps: calcining 1, 3, 5, 6, 7, 10-tetracarboxylic dianhydride and melamine at a high temperature, and reacting according to a stoichiometric ratio of 1: 1 to obtain the covalent organic framework material, wherein PTCA-COF is positively charged and is rich in carboxyl. In a pi-pi bonding path, gold nanoparticles are used as a conducting medium, so that the conductivity of the material is greatly improved, the light absorption efficiency of the ruthenium complex can be synchronously improved by plasma resonance on the metal surface, and the ruthenium complex is suitable for the fields of photoelectric devices such as organic light emitting diodes and flexible electrodes; in the covalent bonding path, the PEI interface modification can avoid agglomeration of the ruthenium compound while immobilizing the ruthenium compound at high density, and the sensor has better long-term stability and can be used for an implantable sensing system.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of optoelectronic functional materials, and specifically relates to two ruthenium composite luminescent materials based on covalent organic framework materials (COFs), which achieve performance improvement through π-π bonding and covalent bonding respectively, and are suitable for fields such as electrochemiluminescence, biosensing and flexible optoelectronic devices. Background Art

[0002] Ruthenium complexes (such as ruthenium bipyridine and its derivatives) are classic and efficient electrochemiluminescent materials with unique advantages in the field of photoelectric sensing, including good water solubility, excellent redox reversibility and electrochemical performance. However, their high water solubility makes the material easy to fall off the surface of solid electrodes, resulting in unstable sensing signals and waste of ruthenium resources. The best way to solve this problem is to find effective carrier materials.

[0003] For example, Chinese patent application publication CN113155916A uses the metal-organic framework material MOF-UiO-67(N) as a solid phase support and introduces a ruthenium-based ligand to form an electrochemiluminescent probe (ruthenium pyridine) in situ. This patent document utilizes the MOF ligand structure to achieve in-situ molecular anchoring, limiting the fixation of the electrochemiluminescent probe while preserving the MOF morphology. However, the inventors of this application have found that the luminescence effect of the probe using this metal-organic framework material MOF-UiO-67(N) as the support material is not strong and the stability needs to be improved.

[0004] Perylene-3, 4, 9, 10-tetracarboxylic dianhydride (PTCDA), an organic dye molecule and organic semiconductor, can form a porous covalent organic framework material after high-temperature condensation with melamine. The inventors of this application discovered that this material has a high specific surface area and a porous structure. Furthermore, through appropriate modification, it can also be endowed with advantages such as adjustable surface functional groups and excellent film-forming properties. Therefore, the inventors of this application attempted to use such a covalent organic framework (COF) material as a carrier material to improve the existing art defects of ruthenium complexes (such as ruthenium bipyridine and its derivatives) that easily fall off the surface of solid electrodes, resulting in unstable sensor signals and waste of ruthenium resources. The goal is to obtain a ruthenium composite luminescent material with high conductivity, stronger luminescence effect, and superior stability. Summary of the Invention

[0005] Based on the above, the present invention proposes using PTCA-COF as a carrier to provide a large number of loading sites for ruthenium complexes while improving the film-forming properties of the material. It also provides methods for preparing two ruthenium composite luminescent materials using different linkers and bonding methods, respectively constructing highly conductive and highly stable materials. To this end, the present disclosure provides the following technical aspects:

[0006] <1> . A multi-mode bonded ruthenium composite luminescent material based on a COF carrier, comprising a covalent organic framework material PTCA-COF and a bipyridine ruthenium compound connected to the PTCA-COF by π-π bonding or covalent bonding, wherein the PTCA-COF is a covalent organic framework material obtained by calcining perylene-3, 4, 9, 10-tetracarboxylic dianhydride and reacting them with melamine in a stoichiometric ratio of 1:1 by molar ratio, and the PTCA-COF is positively charged and rich in carboxyl groups.

[0007] <2> . according to <1> The multi-mode bonded ruthenium composite luminescent material based on the COF carrier, wherein the mass ratio of the bipyridine ruthenium compound to the covalent organic framework material PTCA-COF is in the range of 1:2 to 14:1.

[0008] <3> . according to <1> The multi-mode bonded ruthenium composite luminescent material based on the COF carrier, wherein the ruthenium bipyridine compound is selected from ruthenium dicarboxylate bipyridine or ruthenium terpyridine compound.

[0009] <4> . according to <1> to <3> The multi-mode bonded ruthenium composite light-emitting material based on a COF carrier as described in any one of the preceding claims, wherein the bipyridine ruthenium compound is bonded to the PTCA-COF through a π-π interaction with negatively charged metal nanoparticles pre-introduced into the PTCA-COF.

[0010] <5> . according to <1> to <3> The multi-mode bonded ruthenium composite light-emitting material based on a COF carrier as described in any one of the preceding claims, wherein the bipyridine ruthenium compound is covalently linked to the pre-modified PTCA-COF through an amide reaction.

[0011] <6> . according to <4> The multi-mode bonded ruthenium composite luminescent material based on the COF carrier, wherein the negatively charged metal nanoparticles are gold nanoparticles, and the mass ratio between the gold nanoparticles and the covalent organic framework material PTCA-COF is in the range of 1:2 to 2:1.

[0012] <7> . according to <5> The multi-mode bonded ruthenium composite luminescent material based on the COF carrier, wherein the pre-modified PTCA-COF is a PTCA-COF modified with polyethyleneimine PEI, and the mass content of the polyethyleneimine is in the range of 20% to 40% relative to the total mass of the PTCA-COF modified with polyethyleneimine PEI.

[0013] <8> A method for preparing a COF-based multi-mode bonded ruthenium composite luminescent material, wherein the COF-based multi-mode bonded ruthenium composite luminescent material is a bipyridine ruthenium composite luminescent material bonded to a covalent organic framework material PTCA-COF via π-π interaction, the method comprising the following steps:

[0014] 1) calcining perylene-3, 4, 9, 10-tetracarboxylic dianhydride and melamine at a stoichiometric molar ratio of 1:1 to obtain a covalent organic framework material PTCA-COF, wherein the covalent organic framework material PTCA-COF is positively charged and rich in carboxyl groups;

[0015] 2) providing an in situ formed gold nanoparticle solution;

[0016] 3) adding the ruthenium bipyridine compound to the gold nanoparticle solution obtained in step 2) in an amount with a mass ratio of the ruthenium bipyridine compound to the gold nanoparticles in the range of 5:1-7:1, so that they are electrostatically bonded to form a Ru-Au complex;

[0017] 4) After the Ru-Au complex is ultrasonically dispersed in water, the ultrasonically uniformly dispersed PTCA-COF solution is added in an amount such that the mass ratio of the bipyridine ruthenium compound to the covalent organic framework material PTCA-COF is within a range of 1:2 to 14:1 to obtain the final product Ru-Au@COF.

[0018] <9> A method for preparing a COF-based multi-mode bonded ruthenium composite luminescent material, wherein the COF-based multi-mode bonded ruthenium composite luminescent material is covalently bonded to a bipyridine ruthenium composite luminescent material on a covalent organic framework material PTCA-COF, the method comprising the following steps:

[0019] 1) calcining perylene-3, 4, 9, 10-tetracarboxylic dianhydride and melamine at a stoichiometric molar ratio of 1:1 to obtain a covalent organic framework material PTCA-COF, wherein the covalent organic framework material PTCA-COF is positively charged and rich in carboxyl groups;

[0020] 2) preparing a solution of the PTCA-COF obtained in step 1) and ultrasonically treating the solution. Then, adding 1-ethyl-(3-dimethylaminopropyl)carbodiimide and N-hydroxysuccinimide to the PTCA-COF solution, wherein the amount of 1-ethyl-(3-dimethylaminopropyl)carbodiimide added is 45:1 to 45:7 based on the mass of the PTCA-COF, and the amount of N-hydroxysuccinimide (NHS) added is 7:1 to 1:1 based on the mass of the PTCA-COF. The PTCA-COF is activated in an ice bath. Polyethyleneimine is then added, and the resulting solid is dispersed in water to obtain a PEI@COF aqueous solution.

[0021] 3) adding 1-ethyl-(3-dimethylaminopropyl)carbodiimide and N-hydroxysuccinimide to the aqueous solution of the ruthenium bipyridine compound, wherein the amount of 1-ethyl-(3-dimethylaminopropyl)carbodiimide added is 2:1 to 4:1 based on the mass of the ruthenium bipyridine, and the amount of N-hydroxysuccinimide added is 0.5:1 to 1:1 based on the mass of the ruthenium bipyridine. They are mixed and stirred to fully activate the ruthenium bipyridine, and then the PEI@COF solution prepared in step 2) is added to the reaction mixture to obtain a Ru-PEI@COF solution.

[0022] <10> . according to <8> or <9> In the method, the high-temperature calcination in step 1) comprises: placing the molten metal in a muffle furnace and calcining at 300-350° C. for about 3.5-4.5 hours, and a heating rate of 4.5-5.5° C. / min. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 Shown are the SEM spectra of Au NPs (a), Ru-Au (b), PTCA-COF (c), and Ru-Au@COF (d); and the EDS spectra of C, O, Au, and Ru elements in Ru-Au@COF;

[0024] Figure 2 The full XPS spectrum of Ru-Au@COF (a) and the fine spectra of Au 4f, C 1s, N 1s, Ru 3p, and O 1s (bf) are shown;

[0025] Figure 3 The Zeta potential changes of PTCDA, PTCA-COF, PEI@COF, and Ru-PEI@COF are shown;

[0026] Figure 4 shows the ECL signal comparison of Au NPs, Ru-Au, and Ru-Au@COF (a); the ECL signal comparison of COF, Ru-COF, and Ru-PEI@COF (b);

[0027] Figure 5 The ECL test results of Ru-Au@COF-1, Ru-Au@COF-2 and Ru-Au@COF-3 prepared in Examples 1, 2 and 3 of the present application are shown;

[0028] Figure 6 The ECL test results of Ru-PEI@COF-1, Ru-PEI@COF-2 and Ru-PEI@COF-3 prepared in Examples 4, 5 and 6 of the present application are shown;

[0029] Figure 7 The ECL detection comparison of the final product Ru-Au@COF-4 prepared in Example 7 of the present application and the product Ru-Au@COF-2 prepared in Example 2 is shown;

[0030] Figure 8 The ECL intensity of the bipyridine ruthenium compound obtained when the covalent organic framework material PTCA-COF is used as a carrier of the ruthenium compound is shown. DETAILED DESCRIPTION

[0031] As mentioned above, perylene-3, 4, 9, 10-tetracarboxylic dianhydride (PTCDA) is an organic dye molecule and organic semiconductor material that can form a porous covalent organic framework (COF) material after high-temperature condensation with melamine. Furthermore, the applicant has discovered that by thoroughly grinding and mixing perylene-3, 4, 9, 10-tetracarboxylic dianhydride (PTCDA) and melamine and then calcining them at a high temperature under appropriate conditions to achieve a stoichiometric ratio of 1:1 (i.e., a stoichiometric ratio calculated by the molar ratio), a covalent organic framework (PTCA-COF) rich in positively charged and carboxyl groups can be obtained. This covalent organic framework (PTCA-COF) has advantages such as a high specific surface area and porous structure, tunable surface functional groups, and excellent film-forming properties. Furthermore, in addition to being rich in carboxyl groups, the resulting covalent organic framework (PTCA-COF) also possesses a π-electron structure. Therefore, utilizing the structural characteristics of the covalent organic framework material (PTCA-COF) obtained in this application, the inventors of this application designed two methods, namely π-π bonding and covalent bonding, to obtain a bipyridine ruthenium compound fixed on the covalent organic framework material (PTCA-COF).

[0032] As an example, a covalent organic framework (PTCA-COF) is prepared as follows: melamine and perylene-3,4,9,10-tetracarboxylic dianhydride are thoroughly mixed and ground in a ball mill at a ratio of approximately 1:1. The mixture is then calcined in a muffle furnace at 300-350°C for approximately 3.5-4.5 hours, for example, 4 hours, at a heating rate of 4.5-5.5°C / min, for example, 5°C / min, to produce a deep red COF material. The molar ratio of melamine to perylene-3,4,9,10-tetracarboxylic dianhydride is 1:1.

[0033] Covalent organic frameworks (PTCA-COFs) are COF-based materials with poor conductivity. Directly loading and immobilizing electrochemiluminescent materials, such as ruthenium bipyridine compounds, improves their stability but results in poor luminescence. Therefore, to address this poor conductivity, the first solution of the present disclosure provides a method for improving the conductivity of covalent organic frameworks through π-π bonding. Specifically, negatively charged metal nanoparticles (e.g., gold nanoparticles) and positively charged ruthenium bipyridine compounds, such as ruthenium dicarboxylate, are introduced into the COF material. These particles first form a complex through electrostatic interactions and then bond to the COF support surface via π-π interactions, forming Ru-Au@COF. The gold nanoparticles not only improve the material's conductivity and electron transfer rate, but also enhance the light absorption of the ruthenium compound through plasmon resonance. This design is the first to synergize a COF support with noble metal nanoparticles for ruthenium compound modification, simultaneously resolving the conflict between loading stability and conductivity in related optoelectronic materials.

[0034] The mass ratio of the positively charged ruthenium bipyridine compound, such as ruthenium bipyridine dicarboxylate, to the covalent organic framework material (PTCA-COF) is in the range of 1:2 to 14:1, i.e., the ratio is in the range of 0.5-14, preferably in the range of 1-7. The mass ratio of the gold nanoparticles to the covalent organic framework material (PTCA-COF) is in the range of 1:2 to 2:1, i.e., the ratio is in the range of 0.5-2, preferably 0.8-1.

[0035] As examples, the negatively charged metal nanoparticles may include gold, silver, platinum, etc., but gold nanoparticles are particularly preferred.

[0036] The particle size range of the metal nanoparticles is not particularly limited, but from the perspectives of optical properties and catalytic activity, it can generally be selected within the range of 2-20 nm. Generally, the gold nanoparticles as a preferred embodiment can be obtained by reducing their precursor substances. As an example of preparing gold nanoparticles, sodium citrate can be used as a reducing agent to reduce chloroauric acid solution to obtain gold nanoparticles. In addition, in the first embodiment of the present disclosure, the surface of the metal nanoparticles is required to be negatively charged.

[0037] As a classic and efficient electrochemiluminescent material, examples of ruthenium complexes include ruthenium bipyridine and its derivatives. However, the ruthenium bipyridine used to meet the first embodiment of the present disclosure requires that it is positively charged, and its examples include dicarboxylic acid bipyridine ruthenium and terpyridine ruthenium compounds. In particular, dicarboxylic acid bipyridine ruthenium can be used. Dicarboxylic acid bipyridine ruthenium is positively charged, which makes it improve the conductivity of COF materials. During the reaction process, ruthenium bipyridine can form a complex by combining with positively charged gold nanoparticles through electrostatic action, and then bond to the COF support surface through π-π action to form Ru-Au@COF, that is, a ruthenium compound fixed on the COF material by gold.

[0038] As a preparation example of the first embodiment of this application, a ruthenium pyridine compound with improved conductivity via gold nanoparticles and immobilized on a covalent organic framework (PTCA-COF) is prepared as follows: a chloroauric acid solution is heated to boiling under stirring and refluxed. Sodium citrate is added, with a mass ratio of chloroauric acid to sodium citrate ranging from 1:3 to 1:10. Stirring and reflux are continued. After cooling to room temperature, a ruthenium dicarboxylate bipyridyl solution is added in appropriate proportions. The reaction is stirred for 40-80 minutes, resulting in a Ru-Au complex through electrostatic binding. The reaction solution is centrifuged to collect a purple-black precipitate. The precipitate is dispersed in ultrapure water, and the ultrasonically homogenized PTCA-COF solution is added. The product, Ru-Au@COF, is stirred at room temperature and then centrifuged to obtain the final product, which is then dispersed in ultrapure water and stored at approximately 4°C.

[0039] Figure 1 The SEM spectra of Au NPs (a), Ru-Au (b), PTCA-COF (c), and Ru-Au@COF (d) are shown; as well as the EDS spectra of C, O, Au, and Ru elements in Ru-Au@COF: indicating that Au NPs with relatively uniform size were synthesized by citric acid reduction ( Figure 1 a), after electrostatic binding with ruthenium compounds, a large number of nanoparticles aggregate together to form the corresponding complex ( Figure 1 b); PTCA-COF easily aggregates in aqueous solution ( Figure 1 c) A large amount of Ru-Au nanocomposites accumulated on the COF surface, confirming the successful bonding between the two ( Figure 1 dh).

[0040] Figure 2The XPS full spectrum of Ru-Au@COF (a) and the fine spectra of Au 4f, C 1s, N 1s, Ru 3p and O 1s (bf) are shown: the peaks of Ru-Au-COF at 84.8, 284, 399, 484 and 532 eV correspond to Au 4f, C 1s, N 1s, Ru 3p and O 1s, respectively. The valence band structure information corresponding to each fine spectrum also confirms the successful synthesis of the material.

[0041] On the other hand, as mentioned above, the inventors of this application have also discovered that a carboxyl-rich covalent organic framework (PTCA-COF) can be obtained by thoroughly grinding perylene-3, 4, 9, 10-tetracarboxylic dianhydride (PTCDA) with melamine and then calcining it at high temperature in a muffle furnace. Therefore, in a second approach, the inventors took advantage of the ease of functionalization of the carboxyl groups on the surface of PTCA-COF and first functionalized it. A ruthenium pyridine compound, acting as a luminescent material, was then immobilized onto the PTCA-COF support, thereby obtaining a ruthenium pyridine compound suitable for use as a high-stability electrochemiluminescence sensor. As an example of this second approach, the inventors used PTCA-COF as a matrix and covalently attached a large amount of ruthenium bipyridine, such as ruthenium dipyridine dicarboxylate, to PTCA-COF modified with imine groups, such as polyethyleneimine (PEI), via an amide reaction, to prepare Ru-PEI@COF. This method combined with PEI interface modification technology achieves high-density covalent immobilization of ruthenium compounds. The resulting composite material has excellent stability and is suitable for high-stability electrochemiluminescence sensors.

[0042] As a classical and efficient electrochemiluminescent material, examples of ruthenium complexes include ruthenium bipyridine and its derivatives. In the second embodiment of the present disclosure, examples of ruthenium bipyridine used include ruthenium dicarboxylate bipyridine and terpyridine ruthenium compounds.

[0043] In a second embodiment of the present disclosure, the modified PTCA-COF may include PTCA-COF modified with an amine group or an imine group, preferably PTCA-COF modified with polyethyleneimine (PEI). More preferably, the polyethyleneimine content in the polyethyleneimine (PEI) modified PTCA-COF is in the range of 20% to 40%.

[0044] As a preparation example, polyethyleneimine (PEI)-modified PTCA-COF is prepared as follows: PTCA-COF is prepared into a solution and sonicated for about 0.5-1.5 hours, for example, 1 hour, and then 1-ethyl-(3-dimethylaminopropyl)carbodiimide (EDC) and N-hydroxysuccinimide (NHS) are added. The solution is activated in an ice bath for about 30-50 minutes, for example, 40 minutes. Polyethyleneimine is added and stirred for 6-8 hours, followed by centrifugal washing with water, and vacuum drying at a high temperature, for example, about 60°C, to obtain a solid, which is then redispersed in an aqueous solution to obtain PEI@COF.

[0045] As a preparation example, Ru-PEI@COF is prepared as follows: 1-ethyl-(3-dimethylaminopropyl)carbodiimide (EDC) and N-hydroxysuccinimide (NHS) are added to an aqueous solution of ruthenium dicarboxylate bipyridyl, and the mixture is stirred to fully activate the carboxyl groups of ruthenium dicarboxylate bipyridyl. The prepared PEI@COF solution is then added to the reaction mixture to obtain a Ru-PEI@COF solution.

[0046] Figure 3 The Zeta potential change diagram of PTCDA, PTCA-COF, PEI@COF and Ru-PEI@COF is shown: the Zeta potential change of the materials at different stages confirms the successful synthesis of the materials.

[0047] Figure 4 shows the ECL signal comparison of Au NPs, Ru-Au and Ru-Au@COF (a); the ECL signal comparison of COF, Ru-COF and Ru-PEI@COF (b): The luminescence performance of the ruthenium composite material prepared by PTCA-COF as a carrier through π-π bonding and covalent bonding is significantly improved.

[0048] In addition to producing a ruthenium bipyridine compound with excellent conductivity and stability, the present applicants have also discovered that the ECL signal of the resulting ruthenium bipyridine compound material immobilized on PTCA-COF increases with increasing COF content. In the ruthenium composite luminescent material based on the covalent organic framework (PTCA-COF) of the present invention, obtained through both π-π bonding and covalent bonding, the PTCA-COF content can be very high. For example, the mass of the covalent organic framework (PTCA-COF) can be more than twice that of the ruthenium bipyridine dicarboxylate.

[0049] From the above, it can be seen that the technical advantages of the present invention are:

[0050] This invention addresses the shortcomings of traditional ruthenium-based luminescent materials, such as their poor film-forming properties and stability, by introducing a COF material with a high specific surface area and porous structure as a matrix. It also provides two synthetic routes for luminescent materials: π-π bonding (conductivity enhancement) and covalent bonding (high stability), allowing for flexible adaptation to different application scenarios. In the π-π bonding pathway, positively charged metal nanoparticles, such as gold nanoparticles, are used as the conductive medium, significantly improving the material's conductivity. Plasmon resonance on the metal surface also enhances the light absorption efficiency of the ruthenium complex, making it suitable for optoelectronic devices such as organic light-emitting diodes and flexible electrodes. In the covalent bonding pathway, PEI interface modification allows for high-density immobilization of the ruthenium compound while preventing its aggregation, resulting in excellent long-term stability and application in implantable sensing systems.

[0051] Example

[0052] Examples 1-3 of Scheme 1 are as follows:

[0053] Example 1: Melamine (60 mg) and perylene-3,4,9,10-tetracarboxylic dianhydride (200 mg) were thoroughly mixed and ground in a ball mill for 30 minutes. The mixture was then calcined in a muffle furnace at 300-350°C for 4 hours (heating rate 5°C / min) to produce a deep red COF material. 100 mL of 0.01% chloroauric acid solution was heated to boiling under stirring, and 3 mL of 1% sodium citrate was added. The mixture was stirred and refluxed for 30 minutes. After cooling to room temperature, 1.5 mL of 50 mM ruthenium dicarboxylate bipyridyl solution was added and stirred for 40-80 minutes. A Ru-Au complex was obtained through electrostatic bonding. The reaction solution was centrifuged and washed three times with water to collect the purple-black precipitate. The precipitate was dispersed in 100 mL of ultrapure water, and 5 mL of ultrasonically homogenized COF solution (1 mg / mL) was added. The mixture was stirred at room temperature for 24 h and washed once by centrifugation. The final product, Ru-Au@COF-1, was dispersed in 10 mL of ultrapure water and stored at 4 °C.

[0054] Example 2: Melamine (60 mg) and perylene-3,4,9,10-tetracarboxylic dianhydride (200 mg) were thoroughly mixed and ground in a ball mill for 30 minutes. The mixture was then calcined in a muffle furnace at 300-350°C for 4 hours (heating rate 5°C / min) to produce a deep red COF material. 100 mL of 0.01% chloroauric acid solution was heated to boiling under stirring, and 3 mL of 1% sodium citrate was added. The mixture was stirred and refluxed for 30 minutes. After cooling to room temperature, 1.5 mL of 50 mM ruthenium dicarboxylate bipyridyl solution was added and stirred for 40-80 minutes. A Ru-Au complex was obtained through electrostatic bonding. The reaction solution was centrifuged and the purple-black precipitate was collected by washing three times with water. The precipitate was dispersed in 100 mL of ultrapure water, and 5 mL of ultrasonically homogenized COF solution (2 mg / mL) was added. The mixture was stirred at room temperature for 24 h and washed once by centrifugation. The final product, Ru-Au@COF-2, was dispersed in 10 mL of ultrapure water and stored at 4 °C.

[0055] Example 3: Melamine (60 mg) and perylene-3,4,9,10-tetracarboxylic dianhydride (200 mg) were thoroughly mixed and ground in a ball mill for 30 minutes. The mixture was then calcined in a muffle furnace at 300-350°C for 4 hours (heating rate 5°C / min) to produce a deep red COF material. 100 mL of 0.01% chloroauric acid solution was heated to boiling under stirring, and 3 mL of 1% sodium citrate was added. The mixture was stirred and refluxed for 30 minutes. After cooling to room temperature, 1.5 mL of 50 mM ruthenium dicarboxylate bipyridyl solution was added and stirred for 40-80 minutes. A Ru-Au complex was obtained through electrostatic bonding. The reaction solution was centrifuged and the purple-black precipitate was collected by washing three times with water. The precipitate was dispersed in 100 mL of ultrapure water, and 5 mL of ultrasonically homogenized COF solution (4 mg / mL) was added. The mixture was stirred at room temperature for 24 h and washed once by centrifugation. The final product, Ru-Au@COF-3, was dispersed in 10 mL of ultrapure water and stored at 4 °C.

[0056] Attachment Figure 5 The ECL detection results of Ru-Au@COF-1, Ru-Au@COF-2, and Ru-Au@COF-3 prepared in Examples 1-3 are shown below. As the COF content increases, the ruthenium compounds and gold nanoparticles loaded on Ru-Au@COF increase, and the ECL signal of the material also increases accordingly.

[0057] Examples 4-7 of Scheme 2 are as follows:

[0058] Example 4: Melamine (60 mg) and perylene-3,4,9,10-tetracarboxylic dianhydride (200 mg) were thoroughly mixed and ground in a ball mill for 30 minutes. The mixture was then calcined in a muffle furnace at 300-350°C for 4 hours (heating rate 5°C / min) to produce a deep red COF material. A 1 mg / mL PTCA-COF solution was sonicated for 1 hour. A 1.0 mL portion was added with 45 mg of 1-ethyl-(3-dimethylaminopropyl)carbodiimide (EDC) and 7 mg of N-hydroxysuccinimide (NHS) and activated in an ice bath for 40 minutes. 3 mL of PEI (10 mg / mL) was added and stirred for 6 hours. The mixture was then washed with water by centrifugation and dried in vacuo at 60°C to obtain a solid. The solid was then redispersed in aqueous solution to produce PEI@COF (1 mg / mL). Prepare 5 mL of 1 mM ruthenium dicarboxylate bipyridyl aqueous solution, add 14.4 mg of EDC and 2.9 mg of NHS, mix and stir for 1 h to fully activate the carboxyl groups, then add 1.5 mL of PEI@COF solution and react for 2 h. Centrifuge and wash with water to prepare 2 mL of Ru-PEI@COF-1 solution, which is stored at 4 °C.

[0059] Example 5: Melamine (60 mg) and perylene-3,4,9,10-tetracarboxylic dianhydride (200 mg) were thoroughly mixed and ground in a ball mill for 30 minutes. The mixture was then calcined in a muffle furnace at 300-350°C for 4 hours (heating rate 5°C / min) to produce a deep red COF material. A 1 mg / mL PTCA-COF solution was sonicated for 1 hour. A 3.5 mL sample was added with 45 mg of 1-ethyl-(3-dimethylaminopropyl)carbodiimide (EDC) and 7 mg of N-hydroxysuccinimide (NHS). The mixture was activated in an ice bath for 40 minutes. 3 mL of PEI (10 mg / mL) was added and stirred for 6 hours. The mixture was then washed with water by centrifugation and dried in vacuo at 60°C to obtain a solid. The solid was then redispersed in aqueous solution to obtain PEI@COF (1 mg / mL). Prepare 5 mL of 1 mM ruthenium dicarboxylate bipyridyl aqueous solution, add 14.4 mg of EDC and 2.9 mg of NHS, mix and stir for 1 h to fully activate its carboxyl group, then add 5 mL of PEI@COF solution and react for 2 h. Centrifuge and wash with water to prepare 2 mL of Ru-PEI@COF-2 solution, which is stored at 4 °C.

[0060] Example 6: Melamine (60 mg) and perylene-3,4,9,10-tetracarboxylic dianhydride (200 mg) were thoroughly mixed and ground in a ball mill for 30 minutes. The mixture was then calcined in a muffle furnace at 300-350°C for 4 hours (heating rate 5°C / min) to produce a deep red COF material. A 1 mg / mL PTCA-COF solution was sonicated for 1 hour. A 7 mL aliquot was added with 45 mg of 1-ethyl-(3-dimethylaminopropyl)carbodiimide (EDC) and 7 mg of N-hydroxysuccinimide (NHS) and activated in an ice bath for 40 minutes. 3 mL of PEI (10 mg / mL) was added and stirred for 6 hours. The mixture was then washed with water by centrifugation and dried in vacuo at 60°C to obtain a solid. The solid was then redispersed in aqueous solution to produce PEI@COF (1 mg / mL). Prepare 5 mL of 1 mM ruthenium dicarboxylate bipyridyl aqueous solution, add 14.4 mg of EDC and 2.9 mg of NHS, mix and stir for 1 h to fully activate the carboxyl groups, then add 10 mL of PEI@COF solution and react for 2 h. Centrifuge and wash with water to prepare 2 mL of Ru-PEI@COF-3 solution, which is stored at 4 °C.

[0061] Attachment Figure 6 The ECL test results of Ru-PEI@COF-1, Ru-PEI@COF-2 and Ru-PEI@COF-3 prepared according to the above embodiments 4-6 are shown as follows. As the COF content increases, the ruthenium compound loaded on Ru-PEI@COF increases, and the ECL signal of the material also improves.

[0062] Example 7: Melamine (60 mg) and perylene-3,4,9,10-tetracarboxylic dianhydride (200 mg) were thoroughly mixed and ground in a ball mill for 30 minutes. The mixture was then calcined in a muffle furnace at 300-350°C for 4 hours (heating rate 5°C / min) to produce a deep red COF material. 100 mL of 0.01% chloroauric acid solution was heated to boiling under reflux with stirring. 3 mL of 1% sodium citrate was added and the mixture was stirred and refluxed for 30 minutes. After cooling to room temperature, 1.5 mL of 50 mM terpyridine ruthenium solution was added and stirred for 40-80 minutes. A Ru-Au complex was obtained through electrostatic bonding. The reaction solution was centrifuged and the purple-black precipitate was collected by washing three times with water. The precipitate was dispersed in 100 mL of ultrapure water, and 5 mL of ultrasonically homogenized COF solution (2 mg / mL) was added. The mixture was stirred at room temperature for 24 h and washed once by centrifugation. The final product, Ru-Au@COF-4, was dispersed in 10 mL of ultrapure water and stored at 4 °C.

[0063] Attachment Figure 7The ECL detection comparison results of Ru-Au@COF-4 prepared in Example 7 and the product Ru-Au@COF-2 in Example 2 are as follows. The ECL luminescence effect of terpyridine ruthenium is slightly worse than that of dicarboxylate bipyridine ruthenium.

[0064] Comparative Example

[0065] In order to verify that the present invention uses the covalent organic framework material PTCA-COF as a carrier of the ruthenium bipyridine compound to obtain a stronger luminescence effect and better stability, the inventors used the metal organic framework material MOF-UiO-67 (N) mentioned in the Chinese patent application publication CN113155916A as a comparative carrier material for comparative testing. The preparation process of the ruthenium bipyridine compound fixed on the carrier used in this comparative example is the same as that of Example 2. The test results are shown in the attached figure. Figure 8 As shown. Figure 8 The results show that in the presence of a co-reactant (potassium persulfate), after 12 consecutive scan cycles, the Ru-Au@COF exhibited excellent luminescence stability, with a relative standard deviation (RSD) of 0.41%. Clearly, the PTCA-COF of this application, when used as a carrier for ruthenium bipyridine compounds, can achieve stronger luminescence and superior stability.

[0066] Industrial Applicability

[0067] Given that the bipyridine ruthenium compound obtained according to the present application using the covalent organic framework material PTCA-COF as a carrier can achieve stronger luminescence effect and better stability, it is expected to have potential huge industrial application prospects in the fields of electrochemiluminescence, biosensors and flexible optoelectronic devices.

Claims

1. A multimodal bonded ruthenium composite luminescent material based on a COF carrier, comprising a covalent organic framework material PTCA-COF and a bipyridine ruthenium compound connected to the PTCA-COF via π-π bonding or covalent bonding, wherein the PTCA-COF is a covalent organic framework material obtained by calcining perylene-3, 4, 9, 10-tetracarboxylic dianhydride at high temperature and reacting it with melamine in a stoichiometric ratio of 1:1 on a molar basis, and the PTCA-COF is positively charged and rich in carboxyl groups.

2. The multi-mode bonded ruthenium composite light-emitting material based on a COF carrier according to claim 1, wherein the mass ratio of the bipyridine ruthenium compound to the covalent organic framework material PTCA-COF is in the range of 1:2 to 14:

1. 3 . The multi-mode bonded ruthenium composite light-emitting material based on a COF carrier according to claim 1 , wherein the ruthenium bipyridine compound is selected from ruthenium dicarboxylate bipyridine or ruthenium terpyridine compound.

4. The multi-mode bonded ruthenium composite light-emitting material based on a COF support according to any one of claims 1 to 3, wherein the ruthenium bipyridine compound is bonded to the PTCA-COF through a π-π interaction with negatively charged metal nanoparticles pre-introduced into the PTCA-COF. 5 . The multi-mode bonded ruthenium composite light-emitting material based on a COF support according to claim 1 , wherein the ruthenium bipyridine compound is covalently linked to the pre-modified PTCA-COF through an amide reaction.

6. The multi-mode bonded ruthenium composite luminescent material based on a COF carrier according to claim 4, wherein the negatively charged metal nanoparticles are gold nanoparticles, and the mass ratio between the gold nanoparticles and the covalent organic framework material PTCA-COF is in the range of 1:2 to 2:

1.

7. The multi-mode bonded ruthenium composite luminescent material based on a COF carrier according to claim 5, wherein the pre-modified PTCA-COF is a polyethyleneimine (PEI)-modified PTCA-COF, and the polyethyleneimine mass content is in the range of 20% to 40% relative to the total mass of the polyethyleneimine (PEI)-modified PTCA-COF.

8. A method for preparing a multi-mode bonded ruthenium composite luminescent material based on a COF carrier, wherein the multi-mode bonded ruthenium composite luminescent material based on a COF carrier is a bipyridine ruthenium composite luminescent material bonded to a covalent organic framework material PTCA-COF through π-π interaction, the method comprising the following steps: 1) calcining perylene-3, 4, 9, 10-tetracarboxylic dianhydride and melamine at a stoichiometric molar ratio of 1:1 to obtain a covalent organic framework material PTCA-COF, wherein the covalent organic framework material PTCA-COF is positively charged and rich in carboxyl groups; 2) providing an in situ formed gold nanoparticle solution; 3) adding the ruthenium bipyridine compound to the gold nanoparticle solution obtained in step 2) in an amount with a mass ratio of the ruthenium bipyridine compound to the gold nanoparticles in the range of 5:1-7:1, so that they are electrostatically bonded to form a Ru-Au complex; 4) After the Ru-Au complex is ultrasonically dispersed in water, the ultrasonically uniformly dispersed PTCA-COF solution is added in an amount such that the mass ratio of the bipyridine ruthenium compound to the covalent organic framework material PTCA-COF is within a range of 1:2 to 14:1 to obtain the final product Ru-Au@COF.

9. A method for preparing a multi-mode bonded ruthenium composite luminescent material based on a COF carrier, wherein the multi-mode bonded ruthenium composite luminescent material based on the COF carrier is covalently bonded to a bipyridine ruthenium composite luminescent material on a covalent organic framework material PTCA-COF, the method comprising the following steps: 1) calcining perylene-3, 4, 9, 10-tetracarboxylic dianhydride and melamine at a stoichiometric molar ratio of 1:1 to obtain a covalent organic framework material PTCA-COF, wherein the covalent organic framework material PTCA-COF is positively charged and rich in carboxyl groups; 2) preparing a solution of the PTCA-COF obtained in step 1) and ultrasonically treating the solution. Then, adding 1-ethyl-(3-dimethylaminopropyl)carbodiimide and N-hydroxysuccinimide to the PTCA-COF solution, wherein the amount of 1-ethyl-(3-dimethylaminopropyl)carbodiimide added is 45:1 to 45:7 based on the mass of the PTCA-COF, and the amount of N-hydroxysuccinimide (NHS) added is 7:1 to 1:1 based on the mass of the PTCA-COF. The PTCA-COF is activated in an ice bath. Polyethyleneimine is then added, and the resulting solid is dispersed in water to obtain a PEI@COF aqueous solution. 3) adding 1-ethyl-(3-dimethylaminopropyl)carbodiimide and N-hydroxysuccinimide to the aqueous solution of the ruthenium bipyridine compound, wherein the amount of 1-ethyl-(3-dimethylaminopropyl)carbodiimide added is 2:1 to 4:1 based on the mass of the ruthenium bipyridine, and the amount of N-hydroxysuccinimide added is 0.5:1 to 1:1 based on the mass of the ruthenium bipyridine. They are mixed and stirred to fully activate the ruthenium bipyridine, and then the PEI@COF solution prepared in step 2) is added to the reaction mixture to obtain a Ru-PEI@COF solution.

10. The method according to claim 8 or 9, wherein the high-temperature calcination in step 1) comprises: The mixture was placed in a muffle furnace and calcined at 300-350° C. for about 3.5-4.5 hours, with a heating rate of 4.5-5.5° C. / min.

Citation Information

Patent Citations

  • Solid-state electrochemical luminescence probe and preparation method thereof

    CN113155916A